THE EFFECTIVENESS OF AUTISM CHARACTER STIMULATION ROOM AT AUTISM SERVICE CENTRE BATAM THROUGH BEHAVIORAL ARCHITECTURE - Mikel Owen; Gladies Imanda Utami Rangkuty (Journal of Architectural Research and Education, 2023)
Autism or commonly referred to as autism spectrum disorder often occurs in children at an early age. Not only that, the symptoms of autism result in the failure of the brain's nervous system and sensory bodies as well as the intellectual decline in individuals who experience it. Sensory malfunctions in the body eventually form 2 characters with different responses to stimuli in a certain environment, namely, hyposensitivity and hypersensitivity. 1 in 500 children in Indonesia is known to have this disorder, so it becomes an issue that is not only developing in the country but has an effect on the world. With a significant increase in the number of autism cases, the need for space will increase. Architects as a profession involved in design play an important role in creating a conducive space for children with autism. However, the space must be adjusted based on the characteristics of autism, so that it can function well for them. This research was conducted by evaluating spaces that have different levels of stimulation in the Batam City Autism Service Center, then developing them. This study also uses a behavioral architectural approach by reviewing the characteristics of people with autism, so that the room can provide comfort for them. The research method used is a qualitative-descriptive form and analyzes the room based on existing criteria. The results of the research are a multifunctional low-stimulus room and a high-stimulus room that can adapt based on variations in activity.